2007
DOI: 10.1007/s11630-007-0105-3
|View full text |Cite
|
Sign up to set email alerts
|

Blade parameterization and aerodynamic design optimization for a 3D transonic compressor rotor

Abstract: The present paper describes an optimization methodology for aerodynamic design of turbomachinery combined with a rapid 3D blade and grid generator (RAPID3DGRID), a N.S. solver, a blade parameterization method (BPM), a gradient-based parameterization-analyzing method (GPAM), a response surface method (RSM) with zooming algorithm and a simple gradient method. By the use of blade parameterization method a transonic compressor rotor can be expressed by a set of polynomials, and then it enables us to transform coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The existence of an optimum maximum thickness location at 55% to 60% chord length for such rotor was hypothesized. Similar results can be found in a recent work (Chen et al, 2007) describing an optimization methodology for the aerodynamic design of turbomachinery applied to a transonic compressor bladings and showing how the thermal loss coefficient decreases with increasing the maximum thickness location for all the sections from hub to tip. Not only the position of maximum thickness but also the airfoil thickness has been showed to have a significant impact on the aerodynamic behaviour of transonic compressor rotors, as observed in an investigation on surface roughness and airfoil thickness effects (Suder et al, 1995).…”
Section: Blade Profiles Studiessupporting
confidence: 88%
“…The existence of an optimum maximum thickness location at 55% to 60% chord length for such rotor was hypothesized. Similar results can be found in a recent work (Chen et al, 2007) describing an optimization methodology for the aerodynamic design of turbomachinery applied to a transonic compressor bladings and showing how the thermal loss coefficient decreases with increasing the maximum thickness location for all the sections from hub to tip. Not only the position of maximum thickness but also the airfoil thickness has been showed to have a significant impact on the aerodynamic behaviour of transonic compressor rotors, as observed in an investigation on surface roughness and airfoil thickness effects (Suder et al, 1995).…”
Section: Blade Profiles Studiessupporting
confidence: 88%
“…The movement of separation lines towards TE has also been reported by Samad et al [3] and Jang and Kim [4] by stacking line optimizations to enhance efficiency. Stacking line and airfoil profile modifications also produce the weaker shock strength [8]. As the blade thickness is changed and the blade is leaned due to optimization, a structural analysis can be performed to check the endurance limit and flutter of blade, this has not been studied in the present work.…”
Section: Resultsmentioning
confidence: 99%
“…Oyama et al [7] reported blade profile modification with the help of B-spline curve of NASA rotor 67 to increase adiabatic efficiency by 2%. Chen et al [8] optimized camber line, thickness distribution and stacking line by polynomial curve to define compressor blade and gained 1.73% improvement of adiabatic efficiency. Maximum camber location effect was studied by Chen et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…From a structural and vibration point of view, blade thickness span wise distribution remains the most influential parameter and following various authors [4,6,9], we also select the blade thickness as a primary variable. Because thickness also influences the aerodynamics of the blade, it clearly carries a strong multidisciplinary coupling, making it a good choice for shared variable.…”
Section: Blade Parameterizationmentioning
confidence: 99%